(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
This paper reported ways of enhancing health data management skills of primary healthcare workers in the light of electronic health records. The article, aimed at combining insights of how electronic health records implementation, bridges different aspects of health data management skills of primary healthcare workers; through objective identification of electronic health records applications, their place in health data management skills and assessment of the effect electronic health records on enhancing health data management skills of primary healthcare workers. The method used for this study are; literature review, theoretical discussion, and qualitative analysis. Inferences drawn from existing literatures and qualitative analysis indicated that, nexus exists between health data management skills of primary healthcare workers and electronic health records as evident in previous research work and case studies. Findings revealed the prevalent electronic health records application packages used by primary healthcare workers for health data management are: District Health Information System (DHIS-2), Mobile Strengthening Epidemic Response System (mSERS) and Surveillance Outbreak Response Management and Analysis System (SORMAS). This study recommended the need for government at all levels to give maximum support and required encouragement to the implementation of electronic health records so as to enhance health data management skills of primary healthcare workers and primary healthcare workers should get acquainted with the use of electronic health records applications, for them to be able to navigate database software successfully in order to enhance their health data management skills. Government should also organize regular training and re-orientation workshop for primary healthcare workers on electronic methods of managing healthcare data for improved health data management skills of primary healthcare workers.